The Role of Merdeka Belajar Kampus Merdeka on Teacherpreneurship Skill PG PAUD Student - Sufiati, Vivi; Susari, Hermawati Dwi; Alfina, Alisa; Damayanti, Dwinda (PIAUD Universitas Islam Negeri Sunan Kudus, 2022)
Teacherpreneurship skills are expected to be possessed by PAUD teachers to answer today's challenges. Teacherpreneurship skills can be developed starting from PG PAUD students, as future PAUD teacher candidates. PG PAUD UNIPMA applied 4 BKP MBKM (student exchanges, internships, research, and entrepreneurship) to develop teacherpreneurship skills. However, it is not yet known how the role of MBKM in realizing this will be. So the question arises how the role of MBKM on teacherprenership skills. This research is a quantitative descriptive study that aims to describe the role of MBKM on teacherpreneurship skills. The research subjects were students of the PG PAUD UNIPMA who participated in the MBKM program and the object was teacherpreneurship skills. Data were collected from teacherpreneurship questionnaire with indicators of role in creativity and effectiveness. The results showed that 61.54% stated that the role of MBKM was good and 38.46 % stated that the role of MBKM was very good for teacherpreneurship skills.